Pentingnya Komunikasi Dalam Struktur Organisasi - Panji Erlangga; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Communication activities always take place in everyday life, from the moment you open your eyes until you go back to sleep. This means that every activity requires communication, either directly or indirectly, both verbally and nonverbally, including in the context of the organization. Organizations make communication one of the elements of administration, even though the role of communication in the organization is much greater and has many benefits that can be achieved, so it is clear that